ESTIMATIVA DE VOLUME INDIVIDUAL DE MOGNO AFRICANO POR MEIO DE REDES NEURAIS ARTIFICIAIS (RNAS) - BARBA, Mário Sérgio Brandão,; FERREIRA, Victória Viédes,; SILGUEIRO, João Manoel Lobo Duarte,; COUTO, Allan Motta, (ANAIS DO ENIC, 2022)
-